Analysis of Commitment Point Attainment in Algae Dividing by Multiple Fission - Kselíková, Veronika; Zachleder, Vilém; Bišová, Kateřina (Methods in molecular biology (Clifton, N.J.), 2022)
This work represents a detailed guide for commitment point analysis in microalgae dividing by multiple fission. The method is based on allowing the committed cells to divide in favorable conditions in the dark. This protocol offers a strategy to monitor cell cycle progression, both in control cultures and cultures treated with compounds affecting cell cycle length and/or progression. As the variety of such compounds is wide, our aim was to make the protocol easily modifiable to various research aims. The technique is easy to follow, low-cost, does not require any special equipment and offers reliable results in a reasonable time. The protocol offers step-by-step instructions, explains the theory behind these steps and offers solutions to some of the problems that may arise during the procedure.
Keywords: Viridiplantae; Chlamydomonas; Commitment point; Cell Cycle; buněčné dělení; Cell cycle; Cell Division; Cell division; Multiple fission; Green algae; buněčný cyklus